Child Marriage: Knowledge, Factors, Consequences and Utilization of Maternal Services among Early Married Women - Budha Magar, Esther; Gupta, Mala; Parajuli, Ashya; Chaudhary, Ranjana; Pandey, Ashok; Bhattarai, Sumesh (Journal of Nepal Health Research Council, 2023)
Background: In 2020, UNFPA estimated additional 13 million child marriage cases in Nepal after a decade of lockdown due to COVID-19 wherein 2020, the data of child marriage before the age of 18 reached 5 million where marriage done before the age of 15 years was 1.3 million as per UNICEF. In Nepal, the legal age for marriage is 20 years. As per the National Criminal Code 2074, article 173 (1,2 and 3), one is imprisoned for three years with a penalty of Rs. 30,000, if found to violate the law: marrying before reaching the legal age. Methods: An analytical cross-sectional study was conducted. The sampling design used for the study was simple random sampling. Out of 9 municipalities in Sindhuli district, Dudhauli municipality was selected by using lottery method. 8 wards out of 14 wards in Dudhauli municipality were selected by using purposive sampling. 160 participants were early married women within the age of 15 to 24 years. Three key stakeholders were selected for Key Informant Interview from the local government level worker, non-Governmental organizations working within the municipality, and Dudhauli Health Post. One focused group discussion was conducted with 6 early married women. All the collected data were analyzed through simple descriptive statistics such as frequency, percentage, mean and inferential statics by using chi-square. For a qualitative study, the information collected from the key stakeholders was documented in narrative form. Results: Seven out of 126 women suffered from miscarriage during their second delivery. There is a significant association between the age of marriage and the number of children (P-value 0.0520) and birth time after marriage (P-value 0.019). The majority, 32.6 percent believes that child marriage can be prevented by children’s counselingConclusions: Only 1.6 percent of early married women faced complications during delivery. Majority of physically active women engaged in agriculture sector (97.5%) did not face any difficulty during delivery. None of the early married women have ever suffered from obstetric fistula despite of early delivery.Keywords: Cause; child marriage; consequence; knowledge; Nepal